2006
DOI: 10.1002/pmic.200500022
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of diverse foreign proteins in viral polyhedra and potential application for protein microarrays

Abstract: Cypoviruses are insect viruses that produce a cytoplasmic crystalline particle called the polyhedron in which progeny virions are occluded. The virion structural protein, VP3, is implicated in the occlusion of viral particles into polyhedra. In this study, we determined the amino acid sequence of VP3 required for occlusion of viral particles into polyhedra and proposed that this sequence could be used as an immobilization signal to direct the stable incorporation of foreign proteins into polyhedra. A large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…A follow-up biochemical study further suggested the existence of a "polyhedrin recognition signal" within amino acid residues 42 to 93 that is sufficient to immobilize foreign proteins tagged by this fragment (7,13). We took note of the fact that some proteins failed to be immobilized (9), suggesting that there could be alternative interpretations for the immobilization. Consistent with our ET data, the atomic model of TP (VP4) derived from an improved cryo-EM map at 3.1-Å resolution showed that the N-terminal segment is almost completely buried within the turret, making it unlikely that this segment binds polyhedrin molecules located in the exterior of the virus (17).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A follow-up biochemical study further suggested the existence of a "polyhedrin recognition signal" within amino acid residues 42 to 93 that is sufficient to immobilize foreign proteins tagged by this fragment (7,13). We took note of the fact that some proteins failed to be immobilized (9), suggesting that there could be alternative interpretations for the immobilization. Consistent with our ET data, the atomic model of TP (VP4) derived from an improved cryo-EM map at 3.1-Å resolution showed that the N-terminal segment is almost completely buried within the turret, making it unlikely that this segment binds polyhedrin molecules located in the exterior of the virus (17).…”
mentioning
confidence: 90%
“…TP is encoded by genome segment 4 and was formerly known as VP3 or V3 in previous literature, but it was renamed to VP4 (i.e., the protein encoded by genome segment 4) for clarity (5,20). In addition to making up the turret/B-spike, VP4, and specifically its N-terminal segment (residues 1 to 79), was shown to "immobilize" foreign proteins onto the polyhedron (8,9), suggesting it may bind polyhedrin within polyhedra. A follow-up biochemical study further suggested the existence of a "polyhedrin recognition signal" within amino acid residues 42 to 93 that is sufficient to immobilize foreign proteins tagged by this fragment (7,13).…”
mentioning
confidence: 99%
“…Immobilization of LIF using VP3 or H1 signals was accomplished by dual infection of the recombinant baculoviruses that express the LIF fusion proteins and a recombinant baculovirus AcCP-H expressing BmCPV polyhedrin. The resulting polyhedra were recovered and purified from Sf21 cells, and detected by western blotting as previous reported in Reference [16]. Polyhedra were stored in distilled water containing penicillin (100 U/mL) and streptomycin (100 mg/mL).…”
Section: Generation Of Lif Polyhedramentioning
confidence: 99%
“…We developed two targeting strategies for the incorporation of foreign proteins into polyhedra. Diverse foreign proteins can be immobilized into polyhedra by fusing a polyhedron-targeting tag sequence at the C-or N-terminus of the foreign protein [16].…”
Section: Introductionmentioning
confidence: 99%
“…The CPVs are distinct from other members of this family because they exhibit a single rather than a double capsid layer and during replication they are commonly embedded within large proteinaceous inclusion bodies called polyhedra [1][2][3][4]. Recently, Coulibaly et al described the 2 Å crystal structures of both recombinant and infectious forms of the silkworm cypovirus polyhedra [5], which spurred the use of CPV polyhedra to immobilize foreign proteins within novel expression systems for analysis at the single-cell level [6][7][8].…”
Section: Introductionmentioning
confidence: 99%